The Differences Between ISO 9000 Certified Companies and Non-ISO Companies in Terms of Employee Job Satisfaction, Commitment and Organizational Performance in Service Industry - Othman, Abdul Kadir (2001)
This study is designed to examine the differences between ISO 9000 certified companies and non-ISO companies in terms of employee job satisfaction and commitment and organisational performance (intention to turnover, perceived absenteeism and work performance) in service organisations. ISO 9000 is one of various strategies used by the organisation in order to improve ways of doing business. It involves change in terms of work environment, culture, structure, and the work itself. ISO 9000 has promised that employees would be more satisfied and committed to the organisation as it encourages employees' participation and involvement in designing their jobs. These promises have yet to be proven. For the purpose of the study, several variables are identified and included in the study. These variables are believed to have potential relationships with job satisfaction,commitment and organisational performance like employee turnover, absenteeism and work performance following an introduction of ISO 9000 in the organisation. The variables concerned are job characteristics, work relationships and employees fundamental employment contract. The subjects for the study are the employees of the service organisations that have implemented ISO 9000 in the last few years and the employees of non-ISO organisations. By focusing on these two types of organisations, we are able to assess the differences between ISO 9000 certified companies and non-ISO companies. Stratified Random Sampling are utilised to select the respondents. Two groups of employees consisting of executives and non-executives were randomly selected. Data from the sample are be analysed using several statistical tools in order to measure the degree of associations and differentiation. The major findings in the study are that job characteristics and perceived absenteeism were found significantly lower in ISO 9000 certified companies than in non-ISO companies. Job characteristics and work relationships were found significantly higher among executives than non-executives were. Moreover, younger/new and single employees were found less satisfied with most aspects of their job and less committed to their organisations compared to older/longer service and married employees. These findings contribute in helping managers in identifying areas seriously affected after the implementation of the quality system and it provides some recommendations in that direction. In addition, the study has established a basis for future research.